Evaluasi Tata Kelola Destinasi Wisata Tebing Breksi di Yogyakarta: Analisis Berdasarkan Indikator Sapta Pesona - Nur Rohman; Sugiarto, Sugiarto; Kiswantoro, Amin; Rudi Susanto, Dwiyono (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
This research aims to evaluate the governance of the Breksi Cliff Tourism destination in Yogyakarta based on the Sapta Pesona indicators. Breksi Cliff, which was originally a mining site, has developed into an attractive geological tourism destination thanks to the creative efforts of the local community. This research used a survey method by distributing questionnaires to 170 tourists who visited Tebing Breksi. The analysis was carried out using Importance Performance Analysis (IPA) to identify gaps between the level of importance and performance of Sapta Pesona indicators consisting of security, order, cleanliness, coolness, beauty, friendliness and memories. The results of the analysis show that most of the indicators are in quadrants I and II, which means they are considered important by tourists but their performance varies. Indicators such as staff knowledge, cleanliness of toilets and environmental planning are considered important and have good performance, while road access and prompt service require improvement. Based on these results, it is recommended to maintain good performance and improve aspects that have not met tourist expectations in order to improve the quality of tourism and the competitiveness of Tebing Breksi as a geological tourism destination.